QUANTITATIVE CHARACTERISTICS OF LABOR POTENTIAL IN AGRICULTURAL SECTOR OF AKMOLA REGION - Belgibayeva A.S.; Ashimova I.D.; Zakirova M.S.; Sabikenov S.N. (Scientific Journal of Pedagogy and Economics, 2021)
This article presents an analysis of the current state of the labor market in Akmola region, which gives not only an idea of the degree of efficiency of its functioning, but also allows you to identify promising areas of its development. Various aspects of forming and managing the labor potential of the agricultural sector are analyzed. Quantitative characteristics of the labor potential allowed us to determine the possibilities of its more rational use. The paper presents the features and trends in the development of the regional labor market. There is the differentiation of labor markets in urban and rural areas. The main directions of the state employment policy in the country, which are aimed at increasing the productively employed population and mass entrepreneurship, are considered. The main task in the use of labor resources is to ensure effective employment of the population, improve the quality and competitiveness of the labor force. The availability of the agricultural organizations with the labor resources, their effective use and high level of labor productivity are important for increasing the volume of production in the agricultural sector of the country and the region. Effective use of the labor potential is one of the most important tasks in the forming of socially oriented state, within the framework of the state policy in Kazakhstan.